Why’s Everybody Always Pickin’ on me? A New Look at Police/Minority Contact - Werling, Robert L.; Cardner, Patricia A. (International Journal of Criminology and Sociology, 2013)
Presently there are two explanations for disproportionate minority/police contact: racism and a belief that minorities commit most crimes and there is a need to focus on those communities. This article examines a third possibility that focuses on policing as a social service and minority use of social services in our society. The research examines policing as a social service and compares minority use of other social services with their use of police services. The research also looks at pulling of police into neighborhoods by measuring calls-for-service in various communities; it examines police resource allocation which, as the research indicates, is significantly based on these calls-for-service; and compares minority use of police services with minority utilization of other social services. The research supports the premise that disproportionate minority contact by police is a social phenomenon that is similar to minority over-utilization of other social services.